Revitalização do sistema de oscilografia da proteção da UHE Tucuruí - BRITO, Christiane Valente (2018)
Currently, power companies are faced increasingly with the requirements of the energy market being required to ensure its customers high levels of continuity and reliability of service provision of electricity and also meet the continuation rates of service established by the Agency regulating the electricity sector (ANEEL - National Electric Energy Agency). To achieve these goals and to invest in the optimization of its transmission and distribution systems, responsible companies have invested in the automation of its operations, seeking alternatives that reduce downtime by permanent faults in power systems. This paper proposes the revitalization of disturbance in the system control rooms (generating units and transmission line) UHE-Tucuruí, for better detection and classification of faults through analog and digital information obtained through the acquisition modules. With the modernization of the protection system using the disturbance will be possible to take more accurate decisions in the power generation environment